2016
DOI: 10.3168/jds.2016-11484
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Relationship between serum cortisol concentration and defensive behavioral responses of dairy cows exposed to natural infestation by stable fly, Stomoxys calcitrans

Abstract: The aim of this study was conducted to evaluate the effect of natural infestation by Stomoxys calcitrans on the behavioral and adrenocortical responses of dairy cattle. Twenty Holstein cows randomly selected were individually sprayed with insecticide once every 7d, whereas no insecticide was applied to the other 20 animals. The average number of flies per cow was estimated daily, and the frequency of fly-avoidance behaviors was measured daily; plasma cortisol concentration was measured each morning. No flies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Stable flies ( Stomoxys calcitrans) are biting flies that feed on blood leading to high stress and elevated cortisol levels which may impact cattle health, productivity and welfare [1]. Previous studies have reported severe reduction in US dairy and beef cattle productivity due to S .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable flies ( Stomoxys calcitrans) are biting flies that feed on blood leading to high stress and elevated cortisol levels which may impact cattle health, productivity and welfare [1]. Previous studies have reported severe reduction in US dairy and beef cattle productivity due to S .…”
Section: Introductionmentioning
confidence: 99%
“…Cattle might differ in how aggressively they engage in fly-repelling behaviors according to their breed, color, parity, productivity, and the number of stable flies attacking them [911]. Fly-repellent behaviors include tail flicking, foot stomping, head tossing, skin twitching, and ear trembling to reduce the fly attack [1, 9, 10, 12]. Additionally, cattle tend to aggregate in a tight group with their heads to the center of the group and their tails to the outside to protect themselves against the stable fly attack displaying a behavior known as bunching [1215].…”
Section: Introductionmentioning
confidence: 99%
“…Cattle often bunch together when attacked by stable flies to avoid being bitten; this often leads to heat stress and reduced feeding [12][13][14]. Serum levels of the stress hormone cortisol increased in dairy cows in response to higher numbers of stable flies on them and their associated fly-dislodging behaviors [15]. Their painful bites can reduce milk production in dairy cows, decrease weight gain in beef cattle and affect feed efficiency [16] with national losses in cattle production for the US alone being over $2 billion [17].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of the concentration in the blood (serum or plasma) of stress hormones has been the method most commonly used to assess the effects of stressors in large free-ranging vertebrates such as ruminants (Keay, Singh, Gaunt, & Kaur, 2006;Sheriff, Dantzer, Delehanty, Palme, & Boonstra, 2011;Vitela-Mendoza, Cruz-Vazquez, Solano-Vergara, & Orihuela-Trujillo, 2016). However, this technique requires capture and handling of animals for sample collection, which can artificially increase biological stress and therefore give biased plasmatic GC concentrations.…”
Section: Introductionmentioning
confidence: 99%